ANALISIS LINK AND MATCH PENDIDIKAN DAN PELATIHAN VOKASI INDUSTRI DI KABUPATEN TEMANGGUNG - Bambang Nurcahya, Said (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2024)
Temanggung Regency, Central Java, has received several domestic investments and foreign investments, this has had an impact on economic development, which has quite large growth, namely 5.20% or above Indonesia's economic growth of 5.05% in 2023. Of course, this development is quite encouraging. To further increase the rate of economic growth, the Temanggung Regency Regional Government is obliged to prepare a workforce of residents with Temanggung Regency ID cards so that the unemployment rate can be reduced and the welfare of the community increases. As an agricultural producing area with world-class achievements such as robusta coffee, Arabica coffee, vanilla tobacco and cloves, and driven by the beverage and food processing industri as well as transportation services, the 2023 Gross Regional Domestic Product of Temanggung Regency is 26.9 trillion. Among several areas of retail wholesale trade, car and motorbike repairs and increasing construction, agricultural commodities are still traded as raw and processed materials so their added value is not yet maximized. For this reason, vocational education and training is needed in accordance with existing industries and increasing awareness of all parties to process agriculture into an industrial scale so that it will be more profitable for the community which will have an impact on economic growth in Temanggung Regency.